Clinical performance of full rehabilitations with direct composite in severe tooth wear patients: 3.5 Years results. (March 2018) - Loomans, B.A.C.; Kreulen, C.M.; Huijs-Visser, H.E.C.E.; Sterenborg, B.A.M.M.; Bronkhorst, E.M.; Huysmans, M.C.D.N.J.M.; Opdam, N.J.M.
Abstract: Objectives: To evaluate the mid-term clinical performance of direct composite restorations placed in patients with pathological tooth wear needing full rehabilitation with an increase of vertical dimension of occlusion. Methods: In a prospective trial 34 patients (34.0 ± 8.4 years; 25 males, 9 females) were treated with a minimal invasive additive technique using composite restorations. The restorative treatment protocol was to provide all teeth with composite build-up restorations in an increased vertical dimension of occlusion (VDO) using the DSO-technique. Recall appointments were planned after 1 month, 1 and 3 years after treatment. Restorations were scored for clinically acceptability (FDI-criteria) and scores 4 and 5 were recorded as clinically unacceptable. Frequencies of failures and Kaplan Meier survival curves are presented and effect of relevant variables was calculated with a multifactorial Cox regression (p < 0.05). Results: 1256 Restorations were placed, 687 anterior, 324 premolar, and 245 molar restorations. After a mean observation time of 39.7 months a total of 69 failures were observed, of which 61 restorations were repaired (score 4) and 8 were replaced (score 5). Most common reasons for failure were (chip) fractures (n = 43) and caries (n = 11). Placement of anterior restorations in two sessions led to significant 4.6 times more failures then placed in one session. Conclusions: In patients with severe tooth wear a full rehabilitation, in an increased vertical dimension of occlusion, direct composite resin restorations show a 94.8% success and 99.3% survival rate after a period of 3.5 years.